Entrepreneurship Training for Mothers: Increasing Independence and Welfare - Munawarah Munawarah; Nurmalawati Nurmalawati; Rizky Maulana; Rauzana Rauzana; Irne Aryanie; Hayanuddin Safri; M. Yusuf (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Entrepreneurship training for mothers is one of the effective ways to improve their independence and welfare. This program aims to provide sufficient skills and knowledge for mothers to start and develop their own businesses. Thus, mothers can increase their income and quality of life, as well as increase awareness and participation in economic activities. This article will discuss the benefits, activities, and results of entrepreneurship training for mothers, as well as conclusions and recommendations for the development of similar programs in the future.